Tensile properties of 7075-T6 and 2024-T3 aluminum-alloy sheet heated at uniform temperature rates under constant load - Heimerl, George J. (National Advisory Committee for Aeronautics, 1955)
Results are presented of tests to determine the effect of heating at uniform temperature rates from 0.2 degrees to 100 degrees F. per second on the tensile properties of 7075-T6 d(75s-T6) and 2024-T3 (24s-T3) aluminum-alloy sheet under constant-load conditions. Yield and rupture stresses, obtained under rapid-heating conditions, are compared with results of elevated-temperature stress-strain tests for 1/2-hour exposure. Master yield-and-rupture-stress curves based on linear temperature-rate parameter are presented with which yield and rupture stresses or temperatures may be predicted for these materials for temperature rates from 0.2 to 100 degrees F per second. A description of the test equipment is included.
NACA TN No. 3462.
Keywords: Aluminum alloys.; Plates (Engineering); Loads (Mechanics); Temperature.; Strains and stresses.; elektronické knihy; electronic books